Evaluation of Palm Kernel Meal as Substitute for Soyabean Meal in the Diet of Growing Cockerels - Ojewola, G.S.; Ozuo, U.K. (International Journal of Poultry Science, 2006)
One hundred and twenty Anak Cockerels were used in a 56-day trial to determine the substitutional value of Palm Kernel meal (PKM) for Soyabean meal in the diet of growing cockerels. The five week-old cockerels were randomly allotted to five dietary treatment groups in which the dietary soyabean meal had been substituted with PKM at 0, 25, 50, 75 and 100%. The diets were respectively designated as diets 1, 2, 3, 4 and 5. The results showed that mean daily body weight gain and feed-to-gain ratio for all the treatments were significantly (P< 0.05) influenced. Birds fed diet 2 had the highest weight gain (1229.17g) followed by birds fed diet 1 (control) while birds fed diets 3, 4 and 5 respectively had their weights depressed. Birds fed diet 2 gave the best feed-to-gain ratio (3.88). The feed cost per kilogramme diet significantly (P< 0.05) decreased with the increasing PKM replacement of soyabean meal. Diet 2 gave the least cost per kg weight gain (N159.90) and the highest accruable revenue (N614.58). From the results of this study, it would appear that substituting 25% of soyabean meal with PKM in growing cockerel diets would not only be economically advantageous but enhanced performance.